What Did Teachers’ Unions Do During the COVID-19 Pandemic? Evidence Based on Returns on Teacher Unionization - Eunice S. Han (COVID)
This study investigates the impact of the COVID-19 pandemic on teachers’ labor market outcomes and estimates the returns on unionization. Using a difference-in-differences approach, I identify the effects of the pandemic on employment, earnings, and other labor market outcomes for unionized teachers relative to their non-unionized counterparts. The findings suggest that unionized teachers experienced greater job security and maintained their pre-pandemic wage premium. The role of unions varies significantly across teacher characteristics. Additionally, unionized teachers were more likely to work remotely and remain employed during the pandemic.